In-situ geological conditions and their controls on permeability of coalbed methane reservoirs in the eastern Ordos Basin - Zhang, Yan; Liu, Jincheng (Frontiers in Earth Science, 2024)
The eastern Ordos Basin plays an important role in China's coalbed methane (CBM) industry, boasting considerable CBM resources and pronounced reservoir heterogeneity, making it an ideal site for comparative research on deep and shallow CBM geology. In order to dissect the fundamental reasons for significant differences in production capacity between blocks and promote mutual learning from successful development experiences, this paper conducts a systematical study on the distribution characteristics of in-situ geological conditions of CBM reservoirs based on extensive well-testing data. Additionally, through coal permeability sensitivity experiments on coal samples with various Ro, max values, burial depths, and initial permeabilities, this study explores the change law of permeability during the process of CBM extraction. The results indicate that as the burial depth of coal seam increases, so do the temperature, pressure, and stress. Moreover, the distribution of geothermal gradient, reservoir pressure gradient, horizontal stress gradient, and lateral pressure coefficient tends to converge with increasing burial depth, with a turning depth typically between 1000 and 1500 m. Coal seams below 1500 m generally exhibit a normal-fault type stress field with normal-overpressure. In-situ permeability decreases with depth, but the permeability in deep stress relief zones can be maintained at a relatively high level. A lower initial permeability corresponds to a smaller stress sensitivity coefficient and reduced temperature sensitivity effects, resulting in slower permeability damage during CBM extraction. However, when the reservoir pressure drops to depletion pressure, the maximum damage rate of permeability increases significantly, underscoring the importance of reservoir reconstruction in deep CBM development. This study provides a theoretical basis for selecting favorable areas for CBM exploration and development, as well as for designing efficient development plans in practice.